Energy-Efficient Hybrid Precoder With Adaptive Overlapped Subarrays for Large-Array mmWave Systems - Guo, Ji-Chong; Yu, Qi-Yue; Meng, Wei-Xiao; Xiang, Wei (IEEE transactions on wireless communications, 2020)
In large-array millimeter-wave (mmWave) systems, hybrid pre-coding is one of the most attractive research topics. This paper first presents a flexible adaptive overlapped subarray (OSA) architecture for the analog precoder, whose architecture can be adjusted by a connection network. An objective function is formulated to maximize the energy efficiency (EE) in consideration of the insertion loss for the proposed adaptive OSA based hybrid precoder. The optimal scheme is intractable to achieve, so that we present a heuristic hybrid pre-coding scheme, where the digital precoder is designed based on the zero-forcing (ZF) rule and the analog precoder is designed based on simplified EE optimization in consideration of the insertion loss. We discuss the effect of non-ideal factors on the EE performance, such as quantized phases, imperfect channel state information (CSI), and faulty switches. Simulation results show that, when the initial transmit power is large, our proposed scheme offers a better EE performance than the fully digital pre-coding scheme and many other popular hybrid pre-coding schemes. Moreover, it is found that faulty switches make the double-edged effect on the EE performance when the numbers of activated phase shifters and combiners are pre-defined.